Penerapan Mindful Learning pada Pembelajaran IPAS - Yulianto Dwi Hartono; Dwi Damayanti ZA; ⁠ Ah. Zahid Mahmud; Siti Nur Laely; Sulasmi Sulasmi; Juwaedi Juwaedi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to explore the implementation of the mindful learning approach in Social Studies education at the Madrasah Ibtidaiyah (Islamic elementary school) level. Employing a qualitative approach, data were collected through in-depth interviews, classroom observations, and document analysis at six madrasahs in Central Java Province. The findings reveal that mindful learning is conducted through three main stages: information, transformation, and evaluation. Each stage is applied using contextual, reflective, and participatory strategies. While the approach positively enhances student engagement and social awareness, it faces several challenges, including limited teacher understanding, time constraints, and academic pressure. This study recommends supportive strategies such as teacher training, the creation of reflective learning environments, and active involvement of parents and communities. Policy implications include curriculum development that accommodates mindfulness, preparation of practical modules, and structural reforms in madrasah education systems. These findings suggest that mindful learning is a promising approach for enhancing the holistic and meaningful quality of Science Studies education.